Biological Effectiveness of Food Additives “Sanjam” During Dysbiosis - Irodakhon Mamatova; Ibragim Askarov (International Journal on Integrated Education, 2022)
The food additive "Sanjam" is used in folk medicine of Uzbekistan to normalize the functional state of the gastrointestinal tract. In order to study the biological effectiveness on the functioning of the gastrointestinal tract of this plant complex, an experiment was conducted. During the experiment, it was revealed that this dietary supplement leads to normalization of the evacuation function of the intestine, reducing the risk of disorders of the gastrointestinal tract, as well as maintaining the proper functioning of the intestine.